Experimental Investigation of Thermal Balance of a Turbocharged SI engine Operating on Natural Gas - Gharehghani, A.; Koochak, M.; Mirsalim, M.; Yusaf, Talal (Elsevier Ltd, 2013)
This paper experimentally investigates the thermal balance and performance of a turbocharged gas spark ignition engine. The First Law of Thermodynamics was used for control volume around the engine to compute the output power, transferred energy to the cooling ﬂuid, exhaust gases and also unaccounted losses through convection and radiation heat transfer. Thermal balance tests were performed for various operational conditions including full and half loads and different cooling ﬂuid temperatures. Results indicate that by increasing engine load and coolant temperature, the percentage of transferred energy to the exhaust gases increased while the percentage of coolant energy decreased. Also, experimental data reveals that using gaseous fuel and a turbocharger (TC) in the engine leads to 4.5% and 4% more thermal efﬁciency than gasoline and natural aspirated (NA), respectively. Also, second law analysis reveals that using a turbocharger leads to a 3.6% increase in exergetic efﬁciency of the engine, averagely. Based on experimental results, an empirical correlation was suggested for computing the energy of exhaust gases which shows good agreement with the experimental data for the majority of operating conditions.